Wide‐Gamut Blended Conjugated Polymer Microspheres. Issue 24 (6th October 2021) - Zhang, Lijuan; Mehreen, Tanisha; Liu, Xiaoyuan; Kumar, Vishal; Vagin, Sergey; Gardner, Kirsty; Wang, Hui; Sun, Xuejun; Wu, Shaoyi; Rieger, Bernhard; Meldrum, Alkiviathes
Abstract: Conjugated polymers (CPs) can potentially provide an alternative to conventional fluorescent microsphere technologies; however, examples of CP microspheres encompassing an extensive range of sizes are few, and wide‐ranging spectral control, as needed for many applications, has never been demonstrated. Blended CP microspheres consisting of individual polymers are synthesized here. They are blended to have widely separated Commission Internationale de l'Éclairage (CIE) color coordinates and a compatible synthesis while at the same time forming well‐defined domain structures. By developing appropriate mixtures of selected blue, green, and red fluorescent CPs, blended CP microspheres are demonstrated to cover an extensive range of color coordinates including white. It is shown that multi‐CP microspheres with core–shell or related structures can provide optimum characteristics, while energy and/or charge transfer in finer mixtures result in microspheres without the desired emission properties. Pre‐ or postprocessing further directs consistent changes in the CP microspheres that ultimately regulate the overall spectral response. This approach can lead to a new class of bright fluorescent microparticles with applications in a wide range of disciplines that demand maximum brightness and highly specific emission spectra. Abstract : Fluorescence imaging shows a set of blended polymer droplets near the point of complete solidification. They have at least two domains consisting of an orange emitting bulk phase and whitish‐blue surface platelets.